P09.40 Prevalence of curable sexually transmitted infections in pregnant women in low- and middle-income countries from 2010–2015: a systematic review. (13th September 2015) - Shull, HI; Klausner, JD
Abstract : Introduction: Globally nearly 17, 000 children under 5 years of age die each day. Preterm delivery is the number one cause of under-5 year mortality. Curable sexually transmitted infections (STIs) in pregnant women, specifically syphilis, Neisseria gonorrhoeae, Chlamydia trachomatis, and Trichomonas vaginalis, have been shown to cause preterm delivery through premature rupture of membranes, preterm labour, chorioamnionitis and congenital infection. There is a strong likely causal association between antenatal STIs and preterm delivery. Treating curable STIs may decrease under-5 year mortality. Our objective was to conduct a systematic review and summarise curable STI prevalence estimates among pregnant women in low- and middle-income countries. Methods: PubMed was searched for studies reporting prevalence statistics for syphilis, Neisseria gonorrhoeae, Chlamydia trachomatis, and Trichomonas vaginalis infections among pregnant women in low- and middle-income countries. Studies published between 1/1/2010–3/1/2015 were included. Abstracts of all search results and the full text of all potentially eligible articles were reviewed. Results: 376 potentially relevant reports were identified. 76 studies met inclusion criteria, providing 116 point prevalence estimates for curable STIs in pregnant women, including a total of 3, 594, 777 women. The median value (range) of the estimates for each STI were as follows: syphilis, 1.9% (0–41.7%);   N. gonorrhoeae, 1.6% (0–19.0%); C. trachomatis, 9.8% (0.1–41.3%); and T. vaginalis, 11.2% (1.0–32.3%). The median prevalence value of any STI was found to be 23.9% (10.3–33.7%). Conclusion: Prevalence rates of curable STIs in pregnant women in low- and middle-income countries range from low to high and vary by country. Median prevalence values, however, are high and suggest a large population-level burden of untreated curable infections in pregnant women. Interventions to screen and treat pregnant women in low- and middle-income countries to reduce preterm delivery and subsequent under-5 years of age mortality need urgent evaluation. Disclosure of interest statement: We have no disclosures to make.